1988
DOI: 10.1007/bf00174506
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting serotonin uptake into human platelets

Abstract: Because of complexities in platelet serotonin uptake dynamics, we studied the influence on the time of day and year as well as the subject's age on uptake parameters. While the assay itself was quite reproducible, and the kinetic parameters of 5 HT uptake were stable over a few days, at a given time, within an individual, the variance was quite large when samples from different times of the day or year or from different individuals were compared. An inverse relationship between Vmax (moles/cell number/time) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Gender effects are small with females having approximately 10% higher whole blood 5-HT levels than males (Cook et al 1988). AfricanAmerican subjects have been reported to have higher whole-blood 5-HT levels in preliminary studies (Cuccaro et al 1993;Cook et al 1995).Seasonal variations have been reported for some parameters related to 5-HT metabolism and function in humans, including both platelet 5-HT uptake (Arora et al 1984;Codd et al 1988;Egrise et al 1986;Marazziti et al 1990), content (Brewerton et al 1993Jakovljevic et al 1997 pramine binding (Egrise et al 1986;DeMet et al 1991). However, the results on circannual changes in platelet 5-HT content have been inconsistent (Brewerton et al 1993;Jakovljevic et al 1997; Wirz-Justice and Puhringer 1978;Mann et al 1992).…”
mentioning
confidence: 99%
“…Gender effects are small with females having approximately 10% higher whole blood 5-HT levels than males (Cook et al 1988). AfricanAmerican subjects have been reported to have higher whole-blood 5-HT levels in preliminary studies (Cuccaro et al 1993;Cook et al 1995).Seasonal variations have been reported for some parameters related to 5-HT metabolism and function in humans, including both platelet 5-HT uptake (Arora et al 1984;Codd et al 1988;Egrise et al 1986;Marazziti et al 1990), content (Brewerton et al 1993Jakovljevic et al 1997 pramine binding (Egrise et al 1986;DeMet et al 1991). However, the results on circannual changes in platelet 5-HT content have been inconsistent (Brewerton et al 1993;Jakovljevic et al 1997; Wirz-Justice and Puhringer 1978;Mann et al 1992).…”
mentioning
confidence: 99%
“…Furthermore, there was a significant difference in age between atopic (35+11 yr) and nonatopic patients (47+ 12 yr). This could explain a higher uptake inhibition for older patients as has previously been described [13]. Finally, it is noteworthy that in the Malmgren et al [7] study there was an aggravation of this inhibition when PRP was diluted in PPP o^ the same subject which, among other serum factors, contained IgE.…”
Section: Discussionmentioning
confidence: 54%
“…It is unlikely that the MIBG uptake we measured after incubation without IgE was dependent on factors known to alter serotonin uptake for the following reasons; the experiments were performed al the same time of day to remove the effect of time on serotonin uptake [13]. The normal subjects we studied belonged to the same age group and were also free of psychiatric illness, both factors altering serotonin uptake [13,14]. Consequently, our results before incubation with IgE are comparable to those described in previous studies [9.10].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported on variations in both central and peripheral SERT binding densities (B max ) as an indication of serotonin (5-hydroxytryptamine, 5-HT) activity in humans. These studies have been made according to season (Egrise et al, 1983;Arora et al, 1984;Whitaker et al, 1984;DeMet et al, 1989;Pine et al, 1995;Spigset et al, 1998), age (Codd et al, 1988;Marazziti et al, 1989), exposure to various pharmacologic challenges (Walker and Humphries, 1984;Chen et al, 1991;Callaway et al, 1994;Mash et al, 2000;Patkar et al, 2003), time of day (Wirz-Justice et al, 1977) and also genetics (Codd et al, 1988;Sher et al, 1999;Sher, 2001).…”
Section: Introductionmentioning
confidence: 99%